Supporting Media for Physics Practicum: The Process of Making and Using a Simple Ticker Timer - Ziadatul Fatimah; Muh. Makhrus; Aris Doyan; Susilawati Susilawati; Dedi Riyan Rizaldi (Unversitas Muhammadiyah Mataram, 2021)
Abstract: Writing this article aims to describe the process of making and using a simple ticker timer in physics practicum activities related to straight motion material. The ticker timer tool is included in one of the tools used in learning to make it easier for students to understand the straight motion material. The ticker timer tool developed is a modification of the ticket timer set using simple and easy-to-obtain materials. The process of making a ticket timer consists of three stages, namely 1). The preparation stage is in the form of tools, materials, and design of the tool model to be developed, 2). The manufacturing stage, and 3). The stage of use applied to measure the phenomenon of regular straight motion and regular change of straight motion. Based on the data obtained at the time of using the tool, it is known that the tool can work and be used to measure the time and speed of an object that is observed under certain conditions so that it can be used as a reference to the teacher in supporting the learning process in the classroom.Abstrak: Penulisan artikel ini bertujuan untuk mendeskripsikan proses pembuatan dan penggunaan alat ticker timer sederhana dalam kegiatan praktikum fisika yang berkaitan dengan materi gerak lurus. Ticker timer termasuk dalam salah satu alat yang digunakan dalam pembelajaran untuk memudahkan siswa dalam memahami materi gerak lurus. Alat ticker timer yang dikembangkan merupakan modifikasi dari ticker timer menggunakan bahan yang sederhana dan mudah didapatkan. Proses pembuatan ticker timer terdiri dari tiga tahapan, yaitu 1). Tahap persiapan berupa alat, bahan, dan desain model alat yang akan dikembangkan, 2). Tahap pembuatan, dan 3). Tahap penggunaan yang diterapkan untuk mengukur fenomena gerak lurus beraturan dan gerak lurus berubah beraturan. Berdasarkan data yang diperoleh pada saat menggunakan alat diketahui bahwa alat dapat bekerja dan digunakan untuk mengukur waktu dan kecepatan suatu benda yang diamati pada kondisi tertentu sehingga dapat dijadikan sebagai acuan kepada guru dalam mendukung proses pembelajaran di kelas.